Modulatory Effects of Achyranthes aspera Extracts Pre-Treatment on Cyclophosphamide Induced Alterations in Lipid Profile Parameters in Albino Rats - Samdershi, Deepshikha (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Cyclophosphamide is one of the widely used chemotherapeutic drugs to treat various sorts of cancer and immune- related diseases. However, its use is restricted due to pro- oxidant activity that can damage healthy cells leading to altered metabolism. The liver becomes a susceptible target for xenobiotics toxicity due to its involvement in metabolic reactions. In the present study, an effort has been made to deduce the effects of pre- treatment with extracts of Achyranthes aspera on lipid metabolism in cyclophosphamide treated rats. 30 male albino rats were randomly divided into 6 groups, namely, group I (VC), group II (CYP), group III (AAML), group IV (AAMS), group V (AAML + CYP) and group VI (AAMS + CYP). Methanolic extracts of leaves and seeds of A. aspera were administered orally at the dose of 400 mg/kg body weight. A single dose of cyclophosphamide was injected intraperitoneally at the dose of 50 mg/kg body weight in rats of group II, V and VI on the 14th day of the experiment. The experiment was conducted for a duration of 16 days. Cyclophosphamide caused a significant elevation in serum level of TC, TG, LDL- C, VLDL- C and the atherogenic index, along with a decline in HDL- C. However, this effect was effectively countered by Achyranthes aspera extracts in pre- treatment groups (V & VI), showing its ameliorative effect against cyclophosphamide induced dyslipidemia and cardio- toxicity. % protection against cardiac risk was more in case of leaf extract pre- treatment. Treatment with extracts only did not show toxic alterations. Achyranthes aspera extracts potentially alleviated the cyclophosphamide- induced disturbances caused in lipid profile markers in albino rats. The anti- dyslipidemic property exhibited by the extracts can be possibly attributed to their phytochemical constituents responsible for anti- oxidative actions. Further pharmacological utilization of the plant warrants more scientific explorations.